Network institutionalism in women’s political interests advocacy for gender-mainstreaming of development in Lampung, Indonesia - Darmastuti, Ari (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
Advancing women’s political interests is not an easy activity to do at least due to two factors.  First, women political representation is low both in national and local level.  Second, women’s political interests is yet acknowledged as  important subject compared to other more salient problems such as economic and political issues.  This paper aims to present a critical analysis of how women put forward their political interests in local level through local legislations.  I use mainly network institutionalism as my theoretical analytical tool. Data came from focussed group discussions (FGDs), interviews, participant observations, as well as documents from and with  women groups in executive and legislative bodies, women  non-government organizations (NGOs), women community based organizations (CBOs), professional groups, and academics.    I argue that despite their differences, women groups were able to set a relatively coherent political agendas in local level in Lampung, Indonesia.  This was shown by their ability to control sub-group identifications and develop a common identity with their slogan “united women will never be defeated” to work together for the success of their political interest advocacy.  It was also shown by their ability to develop mutual obligations and reciprocities for the success of the advocacy of the new Lampung Province Regulation on Gender-mainstreaming of Development.